Numerical simulation and the gradient - Performance analysis in table tennis - Wenninger, S.; Lames, M. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The aim of this study was to identify the impact of stroke lengths on the winning probability in table tennis. The performance analysis was done by mathematical simulation using a Markov chain model. 259 high-level table tennis games were evaluated by means of a new simulation approach using numerical derivation to remove the necessity to perform a second modeling step in order to determine the difficulty of tactical behaviors. Based on the derivation, the gradient is used to find differences between strokes in table tennis. Factor extraction by principal component analysis reveals four main components of performance, with long rallies as the most influencing game situations.